A long‐term evaluation of applied nucleation as a strategy to facilitate forest restoration. Issue 1 (January 2016) - Corbin, Jeffrey D.; Robinson, George R.; Hafkemeyer, Lauren M.; Handel, Steven N.
Abstract: Applied nucleation is a restoration technique that seeks to facilitate woody‐plant establishment by attracting birds or other animals that may introduce seeds of dispersal‐limited species. In 1991, an experimental test of applied nucleation was initiated in an abandoned landfill in New Jersey, USA. Trees and shrubs were planted into 16 10 × 10 m plots, covering <3% of the 6‐ha site. In 2010–2011, we sampled the plant community to test the impact of the treatments on forest cover and plant biodiversity. Site‐wide forest cover increased substantially in the 19 years since planting from none to 59%. The original planted plots had significantly higher stem density, particularly of bird‐dispersed species, than unplanted areas. Species composition outside the planted plots was dominated by the wind‐dispersed Fraxinus americana and several small‐seeded bird‐dispersed species, but there were few species indicative of later successional stages. The expected model of successional development via the nucleation model that rates of colonization would be highest near plantings and that forest cover would spread outward from established clusters was not supported after this time span. Given the site's isolation from potential sources of woody propagules, the experimental treatments may not have been enough to overcome many species' dispersal limitation. Regardless of the mechanism, however, the treatments transformed the once essentially treeless site into a densely wooded habitat, and did so at a rate faster than other descriptions of reforestation following disturbances or land‐use changes in the region. Despite the relatively low species richness of the community, this experiment demonstrated that reforestation of even severely degraded habitat can be achieved with minimal management after site preparation and cluster plantings.